2015
DOI: 10.1002/stem.2028
|View full text |Cite
|
Sign up to set email alerts
|

The SCL/TAL1 Transcription Factor Represses the Stress Protein DDiT4/REDD1 in Human Hematopoietic Stem/Progenitor Cells

Abstract: Hematopoietic stem/progenitor cells (HSPCs) are regulated through numerous molecular mechanisms that have not been interconnected. The transcription factor stem cell leukemia/T-cell acute leukemia 1 (TAL1) controls human HSPC but its mechanism of action is not clarified. In this study, we show that knockdown (KD) or short-term conditional over-expression (OE) of TAL1 in human HSPC ex vivo, respectively, blocks and maintains hematopoietic potentials, affecting proliferation of human HSPC. Comparative gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…mice leads to defects in the selection and differentiation of thymocytes (Aspland et al, 2001). The TAL1 is the master regulator of hematopoietic stem/progenitor cells in humans (Benyoucef et al, 2015) and it is essential to formation but not involved in the maintenance of hematopoietic stem cells in adults (Capron et al, 2006). Gene PAX5 is involved in the entry of common lymphoid cells into B cell line.…”
Section: Resultsmentioning
confidence: 99%
“…mice leads to defects in the selection and differentiation of thymocytes (Aspland et al, 2001). The TAL1 is the master regulator of hematopoietic stem/progenitor cells in humans (Benyoucef et al, 2015) and it is essential to formation but not involved in the maintenance of hematopoietic stem cells in adults (Capron et al, 2006). Gene PAX5 is involved in the entry of common lymphoid cells into B cell line.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that REDD1mediated autophagy may be a novel target to sensitize BUC cells to Taxol chemotherapy. REDD1 expression can be induced by MAPK and PKA signaling pathways (42,43), and can also be negatively regulated by other factors such as Ezrin, T-cell acute leukemia 1 (TAL1), and IL6 (44)(45)(46). Here we make the novel discovery that REDD1 is negatively regulated by miR-22.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, there is less understanding of REDD1 inhibitory mechanisms. To the best of our knowledge, only one study reported a REDD1 repression by a transcription factor in human hematopoietic stem cells (43). Our data indicates that REDD1 is expressed at high levels in normal articular cartilage.…”
Section: Discussionmentioning
confidence: 99%